2020
DOI: 10.1186/s12916-020-01805-5
|View full text |Cite
|
Sign up to set email alerts
|

The nSMase2/Smpd3 gene modulates the severity of muscular dystrophy and the emotional stress response in mdx mice

Abstract: Background Duchenne muscular dystrophy (DMD) is a progressive, degenerative muscular disorder and cognitive dysfunction caused by mutations in the dystrophin gene. It is characterized by excess inflammatory responses in the muscle and repeated degeneration and regeneration cycles. Neutral sphingomyelinase 2/sphingomyelin phosphodiesterase 3 (nSMase2/Smpd3) hydrolyzes sphingomyelin in lipid rafts. This protein thus modulates inflammatory responses, cell survival or apoptosis pathways, and the secretion of extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…A recent paper from Gartz et al (2020), showed that GW4869 treatment to reduce exosome release (by neutral sphingomyelinase [nSMase] inhibition) in mdx mice (a popular model of DMD) was protective against cardiac stress, which authors attributed to miR cargo. In line with this, Matsuzaka et al (2020) showed that ablation of nSMase2/Smpd3 gene in mice with a mdx background decreased muscle inflammation and improved functionality.…”
Section:  Skeletal Musclesupporting
confidence: 57%
See 1 more Smart Citation
“…A recent paper from Gartz et al (2020), showed that GW4869 treatment to reduce exosome release (by neutral sphingomyelinase [nSMase] inhibition) in mdx mice (a popular model of DMD) was protective against cardiac stress, which authors attributed to miR cargo. In line with this, Matsuzaka et al (2020) showed that ablation of nSMase2/Smpd3 gene in mice with a mdx background decreased muscle inflammation and improved functionality.…”
Section:  Skeletal Musclesupporting
confidence: 57%
“…In line with this, Matsuzaka et al. ( 2020 ) showed that ablation of nSMase2/Smpd3 gene in mice with a mdx background decreased muscle inflammation and improved functionality.…”
Section: Musculoskeletal Pathologymentioning
confidence: 76%
“…Rescuing the behavioral stress response of mdx mice is thought to occur through normalization of GABAergic receptor expression, 8 brain-derived neurotrophic factor 19 and skeletal muscle-driven regulation of blood pressure. 11 Our metabolomic profiling data from stress-resistant and stress-sensitive male and female mdx mice confirms the role of hemodynamics in the behavioral stress response of mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…The hyper-exaggerated stress response of mdx mice manifests as acute physical inactivity after scruff restraint, forced downhill treadmill exercise or social defeat (severe psychosocial stress in rodents based on dominance and social hierarchy in males). 11,13,17,18 The stress response is associated with altered spatial localization of GABAergic receptors in the brain, 8 expression of the nSMase2/ Smpd3 gene 19 and hyper-activation of the hypothalamicpituitary-adrenal (HPA) axis. 11,13 However, there is now evidence indicating scruff restraint and social defeatinduced physical inactivity in mdx mice is linked to a loss in mean arterial blood pressure with concurrent tachycardia, a perturbation that can result in a 70% mortality rate after social defeat.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to elucidate the relationship between the release of myomiRs via EV and DMD pathogenesis, GW4869 (an inhibitor of nSMase2/Smpd3) was administered to mdx mice. It has been shown that the inhibition of nSMase2/Smpd3 enzymatic activity ameliorates skeletal muscles of muscular dystrophy in mdx mice, in turn, inhibits ceramide synthesis [150]. However, there are problems with the GW4869 inhibitor, in that it has effects on other nSMase2/Smpd3 family members and relatively short-term inhibitory effects.…”
Section: Neutral Sphingomyelinase 2/sphingomyelin Phosphodiesterase 3 (Nsmase2/smpd3) and Dmdmentioning
confidence: 99%